Recurrent abdominal pain in children - Pitono Soeparto; Liek Djupri; Rustiadji Rustiadji; Harjoga Sandi (Paediatrica Indonesiana, 1981)
A total of 48 children aged between 3-12% years, who had complained of at least three episodes of abdominal pain in a period of longer than 3 months, underwent investigations.Routine studies included: blood exam, stool and urine analysis and G.l. X-ray series. EEG, lVP and gall bladder study were occasionally performed.Of the 48 patients studied, 25 (52.1%) were of unknown cause, 11 (22.9%) had emotional disorders, 6 (12.5%) had allergic disorders, 3 (6.3%) had ulcers, 2 (4.2%) had epilepsy and (2.1%) had narrowing of the duodenum.Treatment consisted mostly of psychological approach supported by symptomatic therapy (antacid + fentonium bromide = ulcesium). The results of treatment were in general satisfactory.Upper G.l. studies appeared still to be of value in children with R.A.P. Besides for detecting. organic causes, it is also of importance as part of the psychological approach to convince both the parents and the child that no real organic disease actually existed.